2016
DOI: 10.1007/s10329-016-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cycle of southern brown howler monkey (Alouatta guariba clamitans) through fecal progestin measurement

Abstract: The ovarian cycle in howler monkeys (genus Alouatta) has beean investigated through several biological parameters (ranging between 16.3 and 29.5 days); however, no data exist concerning the ovarian activity of the southern brown howler monkey (Alouatta guariba clamitans). This study aimed to describe the ovarian cycle of A. g. clamitans by profiling fecal progestin concentrations. Over 20 weeks, fecal samples of eight captive adult females of A. g. clamitans were collected. The collections were made at dawn, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Kaiser (1947) evaluated the uterus of the mantled howler ( Alouatta paliatta ) and did not observe spiral or analogous arteries in the endometrium. Contrary, other studies report the presence of erythrocytes in the vaginal lumen at the end of the luteal phase, suggesting that this species has a menstrual cycle (Kugelmeier et al, 2011; Silvestre et al, 2017). Similar features were reported in the Geoffroy's spider monkey ( Ateles geoffroyi ), spiral arteries were also absent in the endometrium and there was mild bleeding with a small number of erythrocytes in the vaginal lumen, suggesting micromenstruation (Hernández‐López et al, 1998).…”
Section: Woolly Monkeysmentioning
confidence: 77%
See 1 more Smart Citation
“…Kaiser (1947) evaluated the uterus of the mantled howler ( Alouatta paliatta ) and did not observe spiral or analogous arteries in the endometrium. Contrary, other studies report the presence of erythrocytes in the vaginal lumen at the end of the luteal phase, suggesting that this species has a menstrual cycle (Kugelmeier et al, 2011; Silvestre et al, 2017). Similar features were reported in the Geoffroy's spider monkey ( Ateles geoffroyi ), spiral arteries were also absent in the endometrium and there was mild bleeding with a small number of erythrocytes in the vaginal lumen, suggesting micromenstruation (Hernández‐López et al, 1998).…”
Section: Woolly Monkeysmentioning
confidence: 77%
“…However, the maintenance of wild species in captivity can produce important reproductive variations due to multiple factors, such as stress, availability of resources, territories, and the composition of social groups (Mayor et al, 2017). Previous research has described different presentations of the sexual cycle depending on the primate species; while the menstrual cycle has been identified in Alouatta guariba clamitans (Silvestre et al, 2017) and genera Aotus , Cebus and Sapajus (de Lima Cardoso et al, 2021; Mayor et al, 2019), Callithrix (Abbott, 1992) and Saimiri (Srivastava et al, 1970) have estrous cycles. However, reproductive knowledge is still absent for many medium‐ and large‐sized primates, such as woolly monkeys (genus Lagothrix ) and uakaris (genus Cacajao ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a large number of studies have demonstrated the reliability of quantifying fecal sex hormone metabolites for assessing female reproductive physiology, in a large number of primate species (e.g. Fürtbauer, Schülke, Heistermann, & Ostner, ; Heistermann et al, ; Scheun et al, ; Silvestre et al, ). This helped to provide important information on basic reproductive characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%